2009
DOI: 10.1007/s12020-009-9240-9
|View full text |Cite
|
Sign up to set email alerts
|

Association studies of interleukin-8 gene in Graves’ disease and Graves’ ophthalmopathy

Abstract: Graves' disease (GD) is an autoimmune disorder, and the most common extrathyroidal manifestation is Graves' ophthalmopathy (GO), which is believed to be caused by a complex interaction between genetic and environmental factors. Many studies have reported that interleukin-8 (IL-8), a potent pro-inflammatory cytokine, is associated with many autoimmune diseases and could increase the degree of lymphocyte infiltration within the thyroid gland. The aim of the present study is to elucidate whether IL-8 is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
0
20
0
5
Order By: Relevance
“…14,28,29 Proinflammatory cytokines, such as IL-6 and IL-8, are strongly associated with development of GO. 30,31 The orbital fibroblasts are the major sources of inflammatory cytokines and have an important role in the development of GO. 32 IL-6, a potent proinflammatory cytokine that activates B-cells to produce functional auto-antibodies, and IL-8, a chemotactic cytokine that recruits T-lymphocytes to the orbital tissue, have promoter regions that possess NFjB binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…14,28,29 Proinflammatory cytokines, such as IL-6 and IL-8, are strongly associated with development of GO. 30,31 The orbital fibroblasts are the major sources of inflammatory cytokines and have an important role in the development of GO. 32 IL-6, a potent proinflammatory cytokine that activates B-cells to produce functional auto-antibodies, and IL-8, a chemotactic cytokine that recruits T-lymphocytes to the orbital tissue, have promoter regions that possess NFjB binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Data from large familial clustering and twin studies suggested that about 80% of the susceptibility to GD may be due to genetic factors with the remainder influenced by environmental or other factors [3]. Many genetic studies on GD have been carried out, and several immune-regulatory candidate genes, such as human leukocyte antigen, cytotoxic T-lymphocyte associated antigen 4 and interleukin-8, have been linked to GD susceptibility [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 105 were duplicated records. From the remaining 280 articles, we found 27 to be relevant according to our study criteria 1 21 22 23 24 25 26 27 28 29 31 32 33 34 35 38 39 40 41 42 43 44 45 46 47 48 49 . We further manually screened the reference lists and identified another 3 relevant studies 30 36 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Emerging studies have shown positive associations of polymorphisms in the IL-related genes (including ILs, interleukin receptors and receptor antagonists) with GO. Over 50 genetic polymorphisms of 17 IL-related genes, namely IL1A 21 22 , IL1B 21 22 23 24 , IL1R 21 , IL1RA 21 25 26 27 , IL2 28 , IL3 29 , IL4 29 30 31 , IL5 29 , IL6 28 32 , IL8 33 , IL9 29 , IL10 31 , IL12B 28 34 35 , IL13 29 30 36 37 38 , IL18 39 , IL21 40 and IL23R 41 42 43 , were reported in GO among different populations. However, the associations of these polymorphisms were inconsistent across different studies.…”
mentioning
confidence: 99%